Factors influencing the return and volatility of georgian stock market - Botsvadze, Ilia (My University, 2012)
Literatürde, hisse senedi getirileri ve makroekonomik değişkenler arasındaki ilişkinin nedensel tarafını keşfetmek için birçok ampirik çalışma vardır. Bu çalışma, Gürcistan 2010:12 etmek 2001:01 dönemini kapsayan aylık veriler uygulayarak, hisse senedi fiyatları ve faiz oranı, enflasyon, döviz kuru ve para arzı gibi makroekonomik faktörler arasındaki nedensel ilişkiyi ele almak istiyor. Kağıt üç bölümden oluşmaktadır: Birinci bölümde genel olarak doğa ve volatilite özelliklerini açıkladı ve hisse senedi piyasası oynaklığını etkileyen makroekonomik faktörleri de son küresel mali kriz geçirerek tartışıldı. İkinci bölümü de Gürcü Sermaye ve Borsası gözden geçirilmesidir. Bölüm üç hisse senedi getirileri ve makroekonomik değişkenler arasındaki ilişkinin nedensel tarafını keşfetmek, Gürcistan Menkul Kıymetler Borsası üzerine ampirik kanıttır. Granger nedensellik modeli böyle ilişkileri keşfetmek için kullanılır. Çalışmanın sonuçları, faiz oranı (INT), enflasyon (TÜFE), para arzı (M2, M1), ve döviz kuru (EXR) hisse senedi getirilerin Granger nedeni olmadığını gösterir ve hisse senedi getirileri para arzı (M2) hariç, makroekonomik değişkenlerin nedeni olmaz. Ayrıca, sonuçların analizi para arzı ve enflasyon Gürcistan'da hisse senedi fiyatlarındaki olumlu belirleyicileri ise faiz oranları ve döviz kuru, hisse senedi fiyatlarındaki olumsuz belirleyicileri olduğunu algılar. Son olarak, hisse senedi getirileri ile makroekonomik faktörleri tahmin kanıtları, makroekonomik değişkenlerin hisse senedi getirilerini tahmin kanıtlardan biraz daha güçlüdür. sse Senedi Getirileri, Makroekonomik Faktörler, Granger Nedensellik, Korelasyon.

In the literature, there are many empirical studies to explore the causal side of relationship between stock returns and macroeconomic variables. However, neither the signs relationship nor the direction of causality is resolved both in theory and in empiric. This study seeks to address the causal relationship between stock prices and macroeconomic factors such as interest rate, inflation, exchange rates and money supply, applying monthly data covering the period of 2001:01 to 2010:12 from Georgia. Paper consists of three chapters, in first chapter generally the nature and the characteristics of volatility is explained, while discussing the macroeconomic factors influencing the stock market volatility as well reviewing volatility under the recent global financial crisis. The second chapter is review of Georgian capital and stock market. Chapter three is empirical evidence on Georgian Stock Exchange, exploring the causal side of relationship between stock returns and macroeconomic variables. Granger causality model is employed to explore such relationships. The results of the study indicate that interest rate (INT), inflation (CPI), money supply (M2, M1), and exchange rate (EXR) do not Granger cause stock returns, as well stock returns do not Granger cause macroeconomic variables in Georgian case, except money supply (M2). Furthermore, the analysis of the results infers that interest rates and exchange rate are the negative determinants of stock prices, while money supply and inflation are the positive determinants of stock prices in Georgia. Finally, the evidence related to predict macroeconomic factors by using stock returns is a little stronger than the evidence related to predict stock returns by applying macroeconomic variables. Key words: Stock Returns, Macroeconomic Factors, Granger Causality, Correlation
Keywords: Hisse Senetleri; Korelasyon; Makroekonomik Faktörler; Muhasebe